Dynamic Properties of Rubber Blends (NR/BR.cis) Under the Effect of Different Blending Ratio and Carbon Black Type - Al-Raheem, Saddam K.; Hassan, Abdul Kareem F.; Jweeg, Muhsin J. (Basrah Journal for Engineering Sciences, 2022)
Due to the wide use of rubber components in different engineering applications such as vibration isolators, engine mounts, car tires, and bridge bearing pads, etc. This rubber component mostly subjected to high levels of vibration and noise which are among the most reasons that lead to the failure of the structures. In the present paper has been performed experimentally to investigate the influences: different content ratios of natural rubber (NR) and polybutadiene (BR.cis) rubber blends [1: (50/50) %, 2: (60/40) %, 3: (70/30) %, 4: (80/20) %, 5: (90/10) %, 6: (100/0) % pphr], and two carbon blacks types (N375, and N220) on the dynamic properties (Rebound Resilience, Damping Time, and Decay Rate). The experimental results showed that the rubber compound that has the blending ratio [1: (50/50) %] has high resilience (low damping), high damping time and high displacement for two carbon black types used in this work. While these properties were improved whenever the rubber blend close to the percentage [5: (90/10) %]. The damping time, amplitude, and resilience of a rubber compound with a blending (90/10) % and carbon black (N220) are decreased by (24.53 %, 36.854 %, and 36.852 %), respectively, compared with a rubber blend that has the blending ratio of (50/50) %.